Abnormally high work hardening ability and excellent comprehensive properties of copper alloys due to multiple twins and precipitates - Ban, Yijie; Zhou, Meng; Zhang, Yi; Jia, Yanlin; Pang, Yong; Li, Yunzhang; Tang, Shunlong; Li, Xu; Volinsky, Alex A.; Marchenko, Ekaterina S. (Materials and design)
In the present work, the Cu-1.35Ni-1Co-0.55Si alloy with multiple twins and ultra-low interfacial mismatch precipitates was obtained by liquid nitrogen dynamic plastic deformation (DPD) and aging treatment. It has abnormally high work hardening ability, which is more than twice that of the previous DPD treatment without aging. In addition, it has excellent comprehensive properties, and its strength, electrical conductivity, and elongation are 816.4 MPa, 40.2% IACS and 11.3% respectively. The fine multiple twins do not coarsen significantly during peak aging, and the dispersed nano precipitates (∼3 nm) further enhance the strength of the Cu-Ni-Co-Si alloy. In addition, the low interfacial mismatch strain between the precipitates and the matrix also ensures adequate elongation. The Cu-Ni-Co-Si alloy has high strength, electrical conductivity, and ductility under the simultaneous action of various mechanisms (grain boundary strengthening, precipitation strengthening, dislocation strengthening and stacking faults). This strategy paves a new avenue for developing precipitation-strengthened alloys with excellent comprehensive properties.